Thermal behavior of ground talc mineral - Balek V.; Šubrt J.; Pérez-Maqueda L.A.; Beneš M.; Bountseva I.M.; Beckman I.N.; Pérez-Rodríguez J.L. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Microstructure development and thermal behavior of ground talc mineral samples (from locality Puebla de Lillo, Spain) was characterized by X-ray diffraction, scanning electron microscopy(SEM),surface area measurements differential thermal analysis, thermogravimetry and emanation thermal analysis (ETA).A vibratory mill and grinding time 5 min. was used to prepare the ground talc sample. It was found that grinding caused an increase in the surface area of the natural talc from 3 m2g-1 to 110 m2g-1. A decrease of particle size after sample grinding was observed by SEM. The increase of structure disorder of the ground sample and the crystallite size reduction from 40 to 10 nm were determined from the XRD results. ETA results revealed a closing up of surface micro-cracks and healing of microstructure irregularities on heating in the range 200-500ºC of both un-ground and ground talc samples. For the ground talc sample a crystallization of non-crystalline phase into orthorhombic enstatite was characterized as by a decrease of radon mobility in the range 785-825ºC and by a DTA exothermal effect with the maximum at 830ºC. ETA results were used for the assessment of transport properties of the talc samples on heating.